Fabrication of Ag/AgI/WO3 heterojunction anchored P and S co-doped graphitic carbon nitride as a dual Z scheme photocatalyst for efficient dye degradation - Hasija, Vasudha; Raizada, Pankaj; Sudhaik, Anita; Singh, Pardeep; Thakur, Vijay Kumar; Khan, Aftab Aslam Parwaz (Solid state sciences, 2020)
Heterojunction formation and non-metal dopant incorporation has been frequently practiced in graphitic carbon nitride (GCN) as a feasible and efficient process for sustaining its inherent metal free properties, while refining its photodegradation ability. In this study, a novel complex ternary PSCN/Ag@AgI/WO3 heterostructure has been obtained from a simple one-pot precipitation method possessing excellent photoactivities for photo removal of toxic malachite green (MG) dye from wastewater utilizing visible-illumination source. SEM images revealed flaky structure of AgI on the monoclinic surface of WO3. The modulated photocatalyst results in suppression of photogenerated electron hole pair recombination as evinced by photoluminescence (PL) spectra and electrochemical impedance spectroscopy (EIS) analysis. The X-ray photoelectron spectroscopy (XPS) results confirmed replacement of corner C atoms and bay carbon atom sites by P dopant whereas, S atoms substituted the N sites in the GCN host lattice framework. Langmuir-Hinshelwood model elucidated that synthesized composite followed pseudo first order kinetics with a rate constant of 0.08 min−1 significant of high stability. The reactive species trapping experiment established that ·OH is the major reactive oxidative species for MG photodegradation. Photodegradation studies revealed 90% removal of MG dye via synthesized ternary PSCN/Ag@AgI/WO3 as compared to 60%, 52%, 50%, 48% and 28% photodegradation over Ag@AgI/WO3, Ag@AgI, WO3, PSCN and GCN, respectively in 60 min of irradiation. Synergistic adsorption, effective dual Z-scheme mechanism was efficient for degradation of MG dye into CO2, H2O, inorganic ions and simpler products and displayed excellent recyclability over ten consecutive cycles. [Display omitted] •Ag/AgI/WO3 was integrated with P and S co-doped g-C3N4.•Dual Z-scheme approach enhances electron-hole pair separation.•The photocatalyst exhibited extended visible light absorption.•Malachite green dye was photo-catalytically eliminated from waste-water.•∙The photocatalyst possessed striking recycle efficiency.